(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
Uzbekistan became the main focus of a number of social diseases in the 50-80s of the 20th century. The widespread spread of tuberculosis in Uzbekistan mainly coincided with the years after the Second World War, Kitab districts of Kashkadarya region and Urgut districts of Samarkand were the main foci of the disease.